The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5492/wjccm.v3.i4.102
|View full text |Cite
|
Sign up to set email alerts
|

Invasive candidiasis in critical care setting, updated recommendations from “Invasive Fungal Infections-Clinical Forum”, Iran

Abstract: Invasive candidiasis (IC) bears a high risk of morbidity and mortality in the intensive care units (ICU). With the current advances in critical care and the use of widespectrum antibiotics, invasive fungal infections (IFIs) and IC in particular, have turned into a growing concern in the ICU. Further to blood cultures, some auxil- REVIEW 102November 4, 2014|Volume 3|Issue 4| WJCCM|www.wjgnet.com iary laboratory tests and biomarkers are developed to enable an earlier detection of infection, however these test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 56 publications
(125 reference statements)
0
13
0
Order By: Relevance
“…We identified 7230 relevant titles and selected 19 CPGs for inclusion ( Figure 1) (Aguado et al, 2011, Alothman et al, 2014, Bassetti et al, 2013, Bow et al, 2010, Chen et al, 2014, Colombo et al, 2013, Cornely et al, 2012, Elhoufi et al, 2014, JSMM, 2013, Kohno et al, 2016, Kung et al, 2018, Limper et al, 2011, Luo et al, 2014, Montravers et al, 2015, Pappas et al, 2016, Ruhnke et al, 2011, Scudeller et al, 2016, Scudeller et al, 2014, Zaragoza et al, 2014. Table 1 presents the main characteristics of included CPGs.…”
Section: Characteristics Of Selected Guidelinesmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 7230 relevant titles and selected 19 CPGs for inclusion ( Figure 1) (Aguado et al, 2011, Alothman et al, 2014, Bassetti et al, 2013, Bow et al, 2010, Chen et al, 2014, Colombo et al, 2013, Cornely et al, 2012, Elhoufi et al, 2014, JSMM, 2013, Kohno et al, 2016, Kung et al, 2018, Limper et al, 2011, Luo et al, 2014, Montravers et al, 2015, Pappas et al, 2016, Ruhnke et al, 2011, Scudeller et al, 2016, Scudeller et al, 2014, Zaragoza et al, 2014. Table 1 presents the main characteristics of included CPGs.…”
Section: Characteristics Of Selected Guidelinesmentioning
confidence: 99%
“…A specific drug was mentioned in seven of the ten guidelines that described prophylaxis: fluconazole was recommended as the initial drug of choice in all seven CPGs (Aguado et al, 2011, Bassetti et al, 2013, Bow et al, 2010, Cornely et al, 2012, Elhoufi et al, 2014, Luo et al, 2014, Pappas et al, 2016. Echinocandin was mentioned as an acceptable alternative in only two CPGs (Bassetti et al, 2013, Pappas et al, 2016.…”
Section: Prophylaxismentioning
confidence: 99%
See 2 more Smart Citations
“…Candida species are common causes of nosocomial infections, with an incidence that has significantly increased in the recent years. It has been reported that Candida is responsible for 9% of all nosocomial bloodstream infections and it is the most common cause of invasive mycoses [3][4][5]. Its crude mortality rate ranges from 40% to 60% and it is ranked as the fourth opportunist infectious agent after Staphylococcus aureus, Pseudomonas Spp, and Escherichia coli in hospitals [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%